Research on network intelligence for 6G - Qingtian WANG; Yang LIU; Haitao LIU; Jiaying ZONG; Fengyi YANG (Dianxin kexue)
Intelligent network has been proposed as early as the 5G era.Towards the 6G era, the network will support more application scenarios and performance requirements.A fully-covered and fully-connected network system requires more intelligent management and maintenance.Firstly, the scope and new application scenarios for 6G networks were introduced, and then the research progress of early-stage network intelligence was summarized.Secondly, the current shortages and supporting technologies of network intelligence for 6G were summarized.Thirdly, the architecture of the intelligent network for 6G and give details about the intelligent function elements were presented, moreover, the use case about the indoor positioning to illustrate the process of network intelligence was given.At last, the evolution route of network intelligence with edge data center was depicted.